Generation of optical pulse packet using a fiber stacker for time fiducial applications. (8th July 2016) - Lin, Honghuan; Wang, Jianjun; Huang, Zhihua; Li, Qi; Xu, Lixin; Tang, Xuan; Li, Chengyu; Guo, Chao; Zhao, Pengfei; Jing, Feng
Abstract: We present the concept of multicolor optical pulse packet generation based on modified fiber stackers featured with reflection geometries. Infrared radiation, visible and ultraviolet time fiducials were obtained by the amplification and frequency-conversion of the pulse packet generated in this fiber stacker. Application for the inertial confinement fusion (ICF) experiment diagnosis with time fiducials was demonstrated. With featured reflection geometries, the shaped packet pulses with uniform sub-pulse polarization states in a temporal window of ns range were generated in the fiber stacker. The design greatly simplifies the packet pulse generation for time fiducial and could be used for laser-driven ICF experimental diagnosis.